Kontribusi Dinas Pendidikan Dayah Aceh dalam Pengembangan Kurikulum Dayah Salafiyah Terpadu - Azhari, Muhammad; Jailani, Jailani (Sekolah Tinggi Agam Islam Sumatera Medan, 2023)
Dayah education is a local wisdom that is owned by the people of Aceh, but in its current development it needs attention from the government. So in this regard this study aims to analyze the contribution of the Dayah Education Office in improving the quality of the Dayah Salafiyah in Aceh Province, one of which is carried out through the development of the dayah curriculum and through improving the quality of the dayah teaching staff so that they have competence in carrying out the dayah curriculum properly in accordance with the standards set by the Aceh Dayak Office. This study uses a qualitative method with a descriptive study approach. The subjects in this study consisted of the Aceh Dayah Education Office, dayah leaders, teaching staff and Dayah administrators. Based on the findings from the field, the implementation of the dayah curriculum has not been maximized, and there are even some dayah who have not yet implemented the curriculum developed by the Aceh Dayah education office. The obstacles to the Dayah Education Office in developing the dayah curriculum in Aceh Province come from internal sources in the form of a lack of funding and the level of human resources of employees, some of whom are still relatively minimal. Meanwhile, external constraints were the lack of participation of the dayah in participating in various socialization activities held by the Dayah Education Office.